"I feel like I am less than other people": Health-related vulnerabilities of male migrants travelling alone on their journey to Europe. (July 2018) - Arsenijević, Jovana; Burtscher, Doris; Ponthieu, Aurelie; Severy, Nathalie; Contenta, Andrea; Moissaing, Stephane; Argenziano, Stefano; Zamatto, Federica; Zachariah, Rony; Ali, Engy; Venables, Emilie
Abstract: During 2015 and 2016, an unprecedented flow of approximately 800, 000 migrants coming from Turkey towards Western Europe crossed the Balkans. Male migrants are perceived as being less vulnerable compared to other migrants and they are not given priority in service and support provision. This qualitative study examines the self-perceived vulnerabilities of male migrants travelling alone along the Balkan route to Europe. Twenty-four individual in-depth interviews, two group interviews and participant observation were conducted with male migrants in Belgrade, Serbia in 2017. Data was coded manually, and analysed thematically. Male migrants traveling alone face the cumulative vulnerability of various traumatic events and migration-related contextual circumstances. Three main themes emerged: the ongoing desperate journey, the better treatment of 'traditionally' well recognised vulnerable sub-groups and the impact of the continuous stress on mental health. Deterrence measures imposed for border control purposes in the form of push-backs, expulsions, detention and degrading, inhumane treatment amplify the psychological distress of male migrants. Feelings of hopelessness, desperation, lack of self-value and self-esteem were reported. 'Traditionally vulnerable' populations were said to have had better treatment throughout the journey from smugglers, border state authorities, governmental officials, civil society and international organizations. The devastating experiences of male migrants, as well as the better treatment offered to other groups of migrants like women and children, results in a perceived neglect of the needs of men in humanitarian response, rendering them vulnerable and exposing them to further health and protection risks. In a context where needs are unmet and people's dignity and health are at risk, specific strategies should be developed to include men in the assistance and protection offered, particularly in relation to exposure to violence. Highlights: Unique insight into health vulnerabilities of male migrants traveling alone. Describes how deterrent migration measures in Europe impact migrants' health. Contributes to understanding prioritization of humanitarian aid provision in Serbia. Emphasises ambiguity of compassionate discourse in contemporary humanitarian action. Argues for individualized vulnerability assessments instead of generalized approach.